Cutaneous metastasis on the nasal tip: first clinical sign of pulmonary carcinoid tumor - Lara Martins Fiorio; Lucia Martins Diniz; Elton Almeida Lucas (Sociedade Brasileira de Dermatologia, 2021)
Abstract Skin metastases are rare and may occur in the context of a known metastatic disease or be the first clinical sign of an underlying primary tumor. In the case of carcinoid neoplasms, determining whether the cutaneous tumor is primary or secondary and identifying the tumor origin in metastatic cases is not always an easy task. This is the report of a case of cutaneous metastasis presenting as the first clinical manifestation of a previously unknown pulmonary carcinoid tumor, including the discussion of histopathological and immunohistochemical findings that allowed an adequate diagnosis of the tumor etiology and reinforces the importance for dermatologists and dermatopathologists to be familiar with these findings.